A minireview on NHE1 inhibitors. A rediscovered hope in oncohematology - Mihaila, Romeo Gabriel (Biomedical papers, 2015)
Background: Na+/H+ exchanger-1 (NHE-1) is involved in pH regulation and is up-regulated in different malignancies. Activation of NHE-1 is one way for allowing cells to avoid intracellular acidification and protect them against apoptosis. Inhibitors of NHE-1 are able to decrease intracellular pH and induce apoptosis. Some statins can also act by partial inhibition of NHE-1. This review presents progress in understanding the mechanisms of action of these inhibitors, connections with certain genetic mutations and acquired treatment resistance, as well as new patents on them.Methods: A MEDLINE search for original and review articles using key terms, Na+/H+ exchanger, leukemia, cariporide, and amiloride. Recent patents with NHE-1 inhibitors published by United States Patent and Trademark Office are also presented.Results and Conclusions: Sorafenib is used for the treatment of acute myeloid leukemia patients carrying internal tandem duplication of fms-like tyrosine kinase 3 (FLT3-ITD) mutation. 5-(N, N-hexamethylene)-amiloride can increase the suppression of FLT3 signaling by sorafenib. NHE-1 inhibitors are able to increase the sensitivity of chronic myeloid leukemia cells to tyrosine kinase inhibitors, including through the inhibition of P-glycoprotein. NHE-1 inhibitors are promising adjuvant drugs for overcoming acquired resistance to treatment in various malignant hemopathies.
Keywords: amiloride; apoptosis; BCR/ABL; cariporide; FLT3/ITD; heme oxygenase-1; leukemia; Na+/H+ exchanger; imatinib mesylate; intracellular pH; isoprenylation; lovastatin; P-glycoprotein; sorafenib; statins